The role of the European Union on immigration: An anthropological approach to the treaties that have been carried out in Europe in order to manage diversity - Carmen Clara Bravo Torres (REGION, 2019)
Migrations are a global phenomenon that has prevailed throughout history. In the last decades there is a need to control every person who enters and leaves the borders of a country. This fact can be observed in the European Union where in the last years the migratory phenomenon is appreciated as a problem. This institution carries out different measures in order to manage this diversity within its borders. However, these agreements are not adapted to the different contexts and are not carried out by all the countries that compose this institution. In spite of all this, the discourse used by the European Union promotes the European identity in front of the rest, differentiating those considered others. These others are differentiated primarily by their nationality although from the discourse analysis can be observed as the economic factor is essential. These themes will be studied in this paper, which will allow us to understand what treaties have been established in the European Union regarding migration and how diversity is managed from them.
Keywords: 330